Smutgrass Control in Perennial Grass Pastures - Brent Sellers; Jason A. Ferrell; J. J. Mullahey (EDIS)
Revised! SS-AGR-18, a 4-page illustrated fact sheet by Brent Sellers, J. A. Ferrell, and J. J. Mullahey, describes the biology and outlines control recommendations for this serious weed of improved perennial grass pastures, roadsides, natural areas, and waste areas in Florida. Published by the UF Department of Agronomy, November 2009.